DESIGNING A CLASSROOM LANGUAGE TEST FOR JUNIOR HIGH SCHOOL STUDENTS - Suwandi Suwandi (Universitas PGRI Semarang, 2010)
Abstract ?é?á This paper attempts to give a scratch of classroom language test design which might be of a great necessity for teachers who want to evaluate their students?óÔé¼Ôäó attainment of their language program. Several important points should be taken into consideration to meet the quality of a language classroom test, among others are the stated objectives in the curriculum, the purpose of the test, the test items used, the test specifications that will reflect both the purpose and the objectives, the kind of scoring, grading, and/or feedback expected. This test design is also done under the basis of School Based Curriculum (KTSP) where discourse competence is of primary objective to be achieved. The competence concerns with the selection, sequencing, and arrangement of words, structures, sentences, and utterances to achieve a unified spoken or written text. ?é?á Key words:?é?á discourse, competence, KTSP, objectives